The evening road - Hunt, Laird (Little, Brown and Company, 2017)
In the summer of 1920 in small-town Indiana, two women--beautiful Ottie Lee Henshaw and Calla Destry, a young black woman--cross paths and they soon move through an America plagued by fear and hatred, determined to flee the secrets they have left behind